2017
DOI: 10.1093/bja/aew312
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic and pharmacodynamic interactions in anaesthesia. A review of current knowledge and how it can be used to optimize anaesthetic drug administration

Abstract: This review describes the basics of pharmacokinetic and pharmacodynamic drug interactions and methodological points of particular interest when designing drug interaction studies. It also provides an overview of the available literature concerning interactions, with emphasis on graphic representation of interactions using isoboles and response surface models. It gives examples on how to transform this knowledge into clinically and educationally applicable (bedside) tools.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
38
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(40 citation statements)
references
References 130 publications
1
38
0
1
Order By: Relevance
“…Besides biomarkers for pain detection under general anesthesia [16], modelling of physiological nociception and drug pharmacokinetics/pharmacodynamics (PK/PD) have a significant impact on anesthesia drug administration [39,40]. The performance of the traditional target-controlled infusion systems for anesthesia can be improved by the real-time adaptation of PK/PD models [41][42][43].…”
Section: Discussionmentioning
confidence: 99%
“…Besides biomarkers for pain detection under general anesthesia [16], modelling of physiological nociception and drug pharmacokinetics/pharmacodynamics (PK/PD) have a significant impact on anesthesia drug administration [39,40]. The performance of the traditional target-controlled infusion systems for anesthesia can be improved by the real-time adaptation of PK/PD models [41][42][43].…”
Section: Discussionmentioning
confidence: 99%
“…Our low end-tidal anaesthetic concentrations and the low mean propofol dosage may be explained by the remifentanil dose we used. 43 As recommended by the ASA guideline, we monitored the depth of anaesthesia using clinical techniques and conventional monitoring systems. 44 We used BIS monitoring as a surrogate indicator of the hypnotic drug effect to enhance the comparability of anaesthesia depth across the groups.…”
Section: Discussionmentioning
confidence: 99%
“… 44 We used BIS monitoring as a surrogate indicator of the hypnotic drug effect to enhance the comparability of anaesthesia depth across the groups. 43 Previous studies have shown a significant lack of homogeneity with regard to the anaesthetics used, and to the best of our knowledge, only one study utilised BIS monitoring. 5 A rapid induction with high desflurane concentrations was avoided because this may enhance the risk of increased inspiratory resistance and consequent upper airway complications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An increasing number of publications deal with the use of dexmedetomidine mainly in the pediatric intensive care unit population—in particular for sedation in hemodynamically unstable patients, such as postcardiac surgery. A recent review of the use of dexmedetomidine in the pediatric population showed that evidence favoring dexmedetomidine in children is mainly extrapolated based on adult studies, small randomized controlled trials, and observational studies . Pediatric trials are therefore needed, with a specific focus on newborns and infants, taking into account the major side effects documented in the literature for dexmedetomidine, hypotension and bradycardia, for which continuous cardiac monitoring is needed.…”
Section: Dose Determination Of Common Analgosedative Drugsmentioning
confidence: 99%